(3JGQjN eUQ GdMOjK hGdeYGUQ ai ebQQGJ GdeOGQS GdeUQjI Hjf GdGMJdGd hGdGSJbdGd (B/s - (3GdHMjQi, Rcis (al-Qahirah : Dar Nahdah al-Sharq, 1996)
Comparative study of the treatment of modern and contemporary Egyptian history in school textbooks before and since the revolution of 1952.
Includes bibliographical references (p. 228-239).
Keywords: Textbooks -- Egypt -- History -- 20th century; Egypt -- History -- 1798- -- Textbooks